Assessment of gene and protein similarities of Beijing-1 vaccine producing strain with Japanese encephalitis virus strains circulating in Vietnam - Thi Ly, Nguyen; Thi Phuong Lien, Huynh; Tuan Dat, Do; Kim Bach, Nguyen; Hoang Tung, Nguyen; Thi Thu, Ha; Duy Khang, Dinh (Vietnam Journal of Biotechnology, 2021)
Since 2006, the inactivated Japanese encephalitis vaccine has been studied and produced by the VABIOTECH company from the Beịing-1 strain on Vero cells. Vaccines produced from the materseed and working seed virus have been evaluated at laboratory and clinical scale in humans. The results showed that the vaccine was safe and created 100% protective antibodies after the booster dose. To officially put this vaccine into production and mass use, the master seed virus BV-MSV-0210 and working seed virus BV-WSV-0310 with the reference standard strain JEV Beijing-Kanonji has been tested for genetic stability. By the method of Sanger sequencing and genetic analysis software, we have evaluated the similarity of nucleotide and proteinsequencesof the E antigen-encoding gene. The results showed that the seed virus similarity of amino acids and nucleotides is 100% compared with the reference strain. Thus, it can be concluded, the seed virus has antigen stability. Nucleotide and amino acid gene sequences of E genomic regions of the two seed lots were compared with virus strains isolated from human, pig and mosquito in Vietnam. The results showed that the nucleotide similarity of seed virus compared with the JEV strains isolated from humans ranged from 86.67 to 97.54%; from pigs is 87.47 to 88.33%, and from mosquitoes is 86.05 to 99%. Meanwhile, the amino acid similarity of the seed virus with the JEV strains isolated from humans ranged from 96.73 to 99.02%; from pigs is 98.00 to98.40% and from mosquitoes 94.55 to 98.40%. The sequence of amino acids in the epitope producing neutralizing antibodies of the seed virus did not differ from that of the JEV strain circulating in humans isolated in 2014.